Review of the Internal Security Act (ISA) / Yvonne How - Yvonne, How (2009)
The papers show the development of the Internal Security Act 1960 (ISA) starting from Karam Singh v Menteri Hal Ehwal Dalam Negeri Malaysia (1969)